VALUE PROPOSITIONS FOR INFORMATION TECHNOLOGY TO IMPROVE HOSPITAL READMISSIONS IN NURSING HOMES. (11th November 2018) - Alexander, G; Galambos, C; Rantz, M; Shumate, S; Murray, C; Wolf, L
Abstract: This report details a qualitative study using an iterative group process bringing together 49 interdisciplinary healthcare stakeholders who are part of the Missouri Quality Improvement Initiative (MOQI). Stakeholders were part of a healthcare network (post-acute/acute), using health information technology (HIT) to reduce avoidable hospitalizations in nursing homes (NH). Group process methods included (1) forming 6 groups with 6–8 stakeholders per group, 2) each group identified changes that HIT contributes toward reducing avoidable hospitalizations, 3) changes identified were then separated by change experienced by stakeholder type, finally, 4) through an iterative consensus building process each group ranked changes identified for each stakeholder type by high, medium, low impact. Stakeholders identified eight common areas of change from HIT use to reduce avoidable hospitalizations in MOQI: Access, Safety, Workflow, Partnerships, Quality of Information, Patient/Family Satisfaction, Legal, and Improved Health. Thirteen stakeholder types were identified that benefit from HIT in MOQI. Within these 13 stakeholder types high impact areas of change were experienced by Directors of Nursing: Administrators, IT/Vendors, Charge Nurses, Admissions Coordinators, Physicians, Social Services, Advanced Practice Nurses, and Care Consultants. Stakeholders experienced high impact change in their ability to perform work using IT to reduce avoidable hospitalizations including: "deep dive into admissions, "; "get a true picture of admission"; "Faster feedback, clarification, authorization"; "Reviewing orders for correctness"; "Provide immediate care". High impact changes contributed to the effectiveness of the MOQI multidimensional intervention including HIT, Advanced Directives, and APRNs working in NH to improve care and help staff better manage resident change in condition.